SERVICE QUALITY CONTROL IN THE DEVELOPMENT OF LANGUAGE LEARNING - Masbahuddin, Masbahuddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to analyze Service Quality Control in the Development of Arabic Language Learning in the Excellent Language of the Zaid bin Tsabit Region. The research approach used is a qualitative descriptive approach with a case study type. Data collection techniques were carried out through interviews, observation, and documentation. Data analysis was carried out in stages, starting from data collection, data presentation, data reduction, and drawing conclusions. The results of the study show that Service Quality Control in the Development of Arabic Language Learning in the Excellent Language of the Zaid bin Thabit Region implements several things, including; 1) Teacher Quality. 2) Learning Materials. 3) Teaching Methods. 4) Learning Environment. 5) Learning Evaluation. By paying attention to these matters, service quality control in the development of Arabic language learning in the Excellent Language of the Zaid bin Thabit Region can be guaranteed so that students can obtain quality and adequate learning